1991
DOI: 10.1302/0301-620x.73b3.1670456
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bone after high-dose irradiation. Biomechanics and histomorphology

Abstract: We studied the effects of high-dose irradiation on the mechanical properties and morphology of cortical bone in rabbits for 52 weeks after a single dose of 50 Gy of elecfron-beam to the tibia. After four weeks, the bending strength of the irradiated bone was unchanged, but at 12 weeks, the strength had decreased significantly. At 24 weeks after irradiation mean strength was less than half of confrols but by 52 weeks there was a tendency toward recovery. Similar, synchronous changes of damage and recovery were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 9 publications
1
70
0
Order By: Relevance
“…We investigated various parameters of strength, composition and formation in cortical bone; the results confirmed that bone loss after proton irradiation is specific to trabecular bone at moderate doses. Other studies investigating cortical bone after irradiation have found changes in cortical bone strength and porosity after very high doses (30,31). However, fractionation of high doses mitigated changes in fracture strength (31), suggesting that lower or fractionated doses of radiation may not affect cortical bone.…”
Section: Discussionmentioning
confidence: 95%
“…We investigated various parameters of strength, composition and formation in cortical bone; the results confirmed that bone loss after proton irradiation is specific to trabecular bone at moderate doses. Other studies investigating cortical bone after irradiation have found changes in cortical bone strength and porosity after very high doses (30,31). However, fractionation of high doses mitigated changes in fracture strength (31), suggesting that lower or fractionated doses of radiation may not affect cortical bone.…”
Section: Discussionmentioning
confidence: 95%
“…However, radiation regimens in these studies differed (eg, no high-dose radiation) from ours and those studies focused on radiation to visceral tumors in the pelvis rather than primary bone tumors. Radiation is a recognized risk factor for the development of insufficiency fractures; it decreases bone strength and the number and resiliency of trabeculae [5,19,21]. It seems plausible that higher doses of radiation would increase the risk of a fracture developing.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that radiation has adverse effects on the biomechanical as well as biological properties of bone [3,12,29]. A canine model has shown that early postoperative irradiation resulted in a substantial reduction in stiffness of the iliac crest strut used for a partial corpectomy defect [3].…”
Section: Discussionmentioning
confidence: 99%